Initial Clinical Manifestations and Early Diagnosis of Basal Cell Skin Carcinoma - Ninković Baroš, Đuka; Lukić, Darko; Jović, Darko; Stanojević, Andrea; Čutura Paurević, Spomenka (Scripta Medica, 2024)
Background/Aim: Basal cell carcinoma (BCC) is the most common cancer of the skin. It is believed that increased UV radiation from the sun accounts for almost 90 % of the risk of BCC. There is a growing trend in the incidence of BCC in a younger population. The aim of study was to analyse the initial clinical symptoms of BCC that may be important for the early detection of this skin tumour.Method: The study was a prospective, multicentre study performed in the period from March 2017 to February 2022. A total of 69 respondents with BCC were analysed. Respondents applied for a targeted examination to examine a suspicious skin lesion (due to certain symptoms) or were diagnosed with BCC by accident, when examining other skin changes. Respondents were divided into 2 groups. The first, Group I (35 respondents), consisted of respondents with nodular BCC. The second, Group II (34 respondents), consisted of respondents with superficial spreading BCC. Initially, a careful history and data on the characteristics, shape and character of the tumour were taken from all respondents. Data on all (even the smallest) initial symptoms and relevant signs of evolution, as well as subjective problems related to the tumour were noted. All respondents underwent dermoscopy of suspected skin changes.Results: A significant difference was found between the examined groups in the characteristics of bleeding, crust formation and tendency to injury in lesions, where they occur more often in patients with nodular BCC. Symptoms such as burning and flaking occurred significantly more often in patients with superficial spreading BCC (p < 0.01), as well as the diameter of lesions over 5 mm (p < 0.05).Conclusion: Early clinical diagnosis of BCC is possible with a tumour diameter of only a few mm. The predominant initial (highly susceptible) symptoms of nodular BCC were initial bleeding and / or scab formation on the lesions, as well as propensity to injury. The superficial spreading form of BCC was often larger than 5 mm in diameter, with more frequent scaling of the lesion, as well as burning and stinging sensations in the tumour area. Itching was observed to be a very common previous occurrence in the BCC initial focus zone in subjects of both study groups. Dermsocopy is a highly reliable diagnostic method for early detection of BCC.